1995
DOI: 10.1055/s-2007-972973
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Daily Voluntary Running onIn VivoInsulin Action in Rat Skeletal Muscle and Adipose Tissue as Determined by the Microdialysis Technique

Abstract: The effect of physical training on in vivo insulin-stimulated glucose utilization in relation to glycolysis (lactate formation) in rat peripheral tissues was investigated in 8 sedentary controls (SC) and 7 voluntary running rats (VR). We used a sequential euglycemic clamp procedure (insulin infusion rate; 6.0, 30.0 mU/kg.min) in combination with a microdialysis technique in M. quadriceps femoris, vastus lateralis, and inguinal adipose tissue. In the clamp study, glucose infusion rate (GIR) averaged over 45-75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Metabolic clearance rate for glucose (MCR, ml´kg ±1´m in ±1 ) was then obtained from GDR divided by the corresponding blood glucose concentration. The GDR and the MCR from 60 to 90 min for the euglycaemic clamp procedure were regarded as indices of insulin action in peripheral tissues, since a plateau glucose infusion rate was achieved during this time, as reported previously [14,15]. In a final group of rats N-monomethyl-l-arginine (l-NMMA, Calbiochem-Novabiochem, Nottingham, England) was infused (1 mg × kg ±1 × min ±1 ) in diabetic rats together with C peptide I (0.05 nmol × kg ±1 × min ±1 ) during low-dose insulin infusion according to the same protocol as described above.…”
Section: Animals and Methodsmentioning
confidence: 99%
“…Metabolic clearance rate for glucose (MCR, ml´kg ±1´m in ±1 ) was then obtained from GDR divided by the corresponding blood glucose concentration. The GDR and the MCR from 60 to 90 min for the euglycaemic clamp procedure were regarded as indices of insulin action in peripheral tissues, since a plateau glucose infusion rate was achieved during this time, as reported previously [14,15]. In a final group of rats N-monomethyl-l-arginine (l-NMMA, Calbiochem-Novabiochem, Nottingham, England) was infused (1 mg × kg ±1 × min ±1 ) in diabetic rats together with C peptide I (0.05 nmol × kg ±1 × min ±1 ) during low-dose insulin infusion according to the same protocol as described above.…”
Section: Animals and Methodsmentioning
confidence: 99%
“…The high-fat-fed rats were further assigned to either a sedentary (n = 7) or a wheel running (n = 7) group [11,12]. The number of exercise wheel revolutions were recorded every day to determine running distance.…”
Section: Methodsmentioning
confidence: 99%
“…A rectal thermometer was introduced and the rectal temperature was kept at 37.0 °C by adjusting the distance from a heating lamp. As previously reported [10,11], microdialysis probes, which consisted of a tubular membrane (polycarbonate, outer diameter 0.5 mm, length 10 mm, molecular weight cut-off 5,000-20,000 daltons, Carnegie Medicin, Sweden), were inserted bilaterally into the quadriceps muscles, vastus lateralis, and were also put into the right jugular vein by using the guide for the blood microdialysis.…”
Section: Experimental Protocolmentioning
confidence: 98%
“…We recently reported that the microdialysis technique can be used to measure intramuscular 3-hydroxybutyrate (3-OHBA) [10] and lactate levels [11]. With this technique, therefore, the present study was undertaken to clarify the effect of tetanic contraction (60 tetani/min) on intramuscular 3-OHBA and lactate levels in diabetic and non-diabetic control rats.…”
mentioning
confidence: 97%